TRADE SPECIALIZATION INDICES: TWO COMPETING MODELS - Samsubar Saleh; Tri Widodo (Journal of Indonesian Economy and Business (JIEB), 2010)
Revealed Comparative Advantage (RCA) index by Balassa (1965) is intensively applied in empirical studies on countries’ comparative advantage or trade specialization.Asymmetric problem in the criteria of RCA index encourages Dalum et al. (1998) and Laursen (1998) to make Revealed Symmetric Comparative Advantage (RSCA) index. Thesetwo indexes are commonly employed in econometric models for analyzing countries’ trade specialization. This paper aims to compare theoretically and empirically the twocompeting econometric models, one using RCA and the other using RSCA. The ASEAN countries’ comparative advantages are presented for the empirical case studies. Thispaper concludes that RSCA can, to some extent, reduce the “outlier problem” of RCA in the econometric model; therefore, the model using RSCA can be more statistically reliablethan the model using RCA. The two econometric models might not be suitable for forecasting purposes since the estimated values could theoretically violate their criteria ofcomparative advantage and disadvantage. In the cases of ASEAN countries, we find empirically that the model using RSCA is statistically more reliable than the one usingRCA. The ASEAN countries have exhibited de-specialization.JEL classification: F10, F14, F17Keywords: Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA).